Non Functional Diagnostic and Super Speciality Block at Govt Medical College Amritsar Punjab - CAG of India (CAG of India)
Guru Teg Bahadur Diagnostic and Superspeciality Block constructed at a cost of INR 24.27 crore could not be made functional for intended purposes for more than three years since its completion due to non-provision of requisite staff and funds by the Department of Medical Education and Research. Audit recommended that the State Government may provide requisite manpower and funds to make the Guru Teg Bahadur Diagnostic and Superspeciality Block functional to deliver envisaged medical facilities to public.